(untitled) (Web of Teachers: Inderscience Research, 2025)
Artificial Intelligence (AI) is transforming many aspects of medicine — not just patient care, but also how medicine is taught. Increasingly, medical schools and educators are exploring how AI can support teaching, assessment, simulation, and student learning. This article reviews recent research on AI in medical education, outlines the opportunities and benefits for medical students, highlights persistent challenges, and offers recommendations for thoughtful integration.